Answer:divide the opposite sides, by the length of the hypotenuse. To get the cosine, divide the length of the adjacent side,by the length of the hypotenuse.
Step-by-step explanation:
divide the opposite sides, by the length of the hypotenuse. To get the cosine, divide the length of the adjacent side,by the length of the hypotenuse.
Answer:
zero.
Step-by-step explanation:
. Here are the steps. h(x) = -5x - 10. h(-2) = -5(-2) - 10. h(-2) = 10 - 10. h(-2) = 0. Have a great day
Variable, because its a letter<span />
<span>(f o g)(-4)
=-4(3x+5)+7
</span><span>=-4(3(-4)+5)+7</span><span>
= 35</span>
Answer:
It look right to me
Step-by-step explanation: